"Home Is Where I Spend My Money": Testing the Remittance Decay Hypothesis with Ethnographic Data from an Austrian-Turkish Community - Meyer, Silke (Social Inclusion, 2020)
Remittances—money sent back by migrants to their place of origin—are considered to be both economic and social practices mapping out a transnational space of migration. By sending and receiving money, objects, ideas, and social norms, migrants and non-migrants strengthen their social ties and express their multiple belongings. Remittances can thus be read as a practice of multi-local participation and inclusion. When remittance develops a negative trend, the remittance decay hypothesis thus concludes a shift in belonging: The longer migrants stay in their host country and build a life there, the less they remit. In this article, the remittance decay hypothesis is tested with ethnographic data from interviews and participant observation in the migration nexus between Uşak, Turkey, and Fulpmes, Austria. Remittance to Turkey has declined markedly in the last two decades from a record high of 574 USD million in September 1998 to a record low of 11 USD million in August 2019. Ethnographic data with members of three generations of Turkish-Austrians in Fulpmes can help to explain this process from a diachronic perspective: for changing remittance practices and a transformation in remittance scripts, e.g., as investment, compensation, help, gift or charity donation, demonstrate that there is more to the story than a fading sense of belonging.